Implementasi Pendidikan Antikorupsi melalui Kurikulum Kearifan Lokal di Sekolah - Anco, Anco (FKIP UNSULTRA, 2026)
The purpose of this study is to analyze the implementation of anti-corruption education through a local wisdom-based curriculum in schools as an effort to build integrity in the young generation. This research employs a literature review method by examining various scientific sources and previous studies relevant to anti-corruption education and local wisdom in Indonesia. The findings indicate that integrating local wisdom values such as honesty, mutual cooperation , responsibility, and justice into the anti-corruption education curriculum has proven effective in enhancing students' understanding and attitudes toward anti-corruption. Implementation strategies include transparent and accountable school management, integration of anti-corruption values into relevant subjects, local content, personal development, and fostering an anti-corruption culture through extracurricular activities. These findings suggest that local wisdom-based anti-corruption education strengthens students' cultural identity while shaping an integrity-driven generation capable of addressing future corruption challenges.